2022
DOI: 10.3389/fonc.2022.915481
|View full text |Cite
|
Sign up to set email alerts
|

Application of artificial intelligence in the diagnosis of subepithelial lesions using endoscopic ultrasonography: a systematic review and meta-analysis

Abstract: Endoscopic ultrasonography (EUS) is the most common method for diagnosing gastrointestinal subepithelial lesions (SELs); however, it usually requires histopathological confirmation using invasive methods. Artificial intelligence (AI) algorithms have made significant progress in medical imaging diagnosis. The purpose of our research was to explore the application of AI in the diagnosis of SELs using EUS and to evaluate the diagnostic performance of AI-assisted EUS. Three databases, PubMed, EMBASE, and the Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
3
1
Order By: Relevance
“…In this validation study, the sensitivities and specificities of the five diagnostic models (GIST, leiomyoma, neuroendocrine neoplasm, ectopic pancreas, and lipoma) were 68.3-95.7% and 64.1-83.3%, respectively. As a meta-analysis of previous EUS image-based AI-assisted diagnostic studies showed sensitivities and specificities of 0.93 (95% confidence interval [CI] 0.93-0.97) and 0.88 (95% CI 0.71-0.96), respectively, 6 the diagnostic results of this study seemed to be somewhat inferior to those of previous studies. However, previous studies were mainly focused on the distinction between GIST and non-GIST, and the results of this study were considered satisfactory for evaluating the EUS findings alone.…”
contrasting
confidence: 95%
See 2 more Smart Citations
“…In this validation study, the sensitivities and specificities of the five diagnostic models (GIST, leiomyoma, neuroendocrine neoplasm, ectopic pancreas, and lipoma) were 68.3-95.7% and 64.1-83.3%, respectively. As a meta-analysis of previous EUS image-based AI-assisted diagnostic studies showed sensitivities and specificities of 0.93 (95% confidence interval [CI] 0.93-0.97) and 0.88 (95% CI 0.71-0.96), respectively, 6 the diagnostic results of this study seemed to be somewhat inferior to those of previous studies. However, previous studies were mainly focused on the distinction between GIST and non-GIST, and the results of this study were considered satisfactory for evaluating the EUS findings alone.…”
contrasting
confidence: 95%
“…Because of these diagnostic difficulties, studies are reporting the use of EUS image-based scoring systems or computer-aided diagnosis, such as artificial intelligence (AI)-aided diagnosis. 5,6 Several similar studies are expected to be conducted in the future.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent meta-analysis of ten studies evaluated the diagnostic accuracy of artificial intelligence in detecting pancreatic cancer using EUS images [39 ▪▪ ], revealing high diagnostic sensitivity (92%) and specificity (90%). Another meta-analysis demonstrated superior performance of CNN models in diagnosing gastro-intestinal subepithelial lesions from EUS images compared to EUS experts without artificial intelligence aids (sensitivity, 93 vs. 71%; specificity 81 vs. 69%) [40].…”
Section: Artificial Intelligence In Endoscopymentioning
confidence: 99%